The effect of soil Treatment system and NPK fertilizer with different dosages on growth and production of tomato plants (Lycopersicum esculentum mill.) - Asfaruddin Asfaruddin; Prihanani Prihanani; Andree Saputra (University of Prof. Dr. Hazairin, SH, 2022)
This study aims to determine the effect of soil management system and dose of NPK fertilizer (15:15:15) on the growth and yield of tomato plants. The experiment used a Split Plot Design with 3 replications. As the main plot, there are types of tillage (P) consisting of 3 levels, namely: P1: No tillage; P2: Minimum Tillage; P3: Maximum Tillage. As a sub-plot, the dose of compound fertilizer NPK (15:15:15) consisted of 4 levels, namely: D0 : No fertilizer (control) equivalent to 0 kg/plot; D1: A dose of 125 kg/ha is equivalent to 37.375 g/plot; D2: The dose of 250 kg/ha is equivalent to 74.75 g/plot; D3: The dose of 375 kg/ha is equivalent to 112.125 g/plot. The results of this study showed that the type of tillage had no significant effect on plant height and number of fruit per plant, but had a very significant effect on fruit weight per plant and fruit weight per plot. Maximum tillage gave the highest fruit weight per plant and fruit weight per plot. The dose of fertilization with NPK compound fertilizer (15:15:15) had no significant effect on plant height, but significantly on the number of fruits per plant, fruit weight per plant and fruit weight per plot. The application of NPK fertilizer at 375 kg/ha gave the highest number of fruit per plant, fruit weight per plant and fruit weight per plot. The interaction between the types of tillage and the dose of NPK compound fertilizer had no significant effect on plant height, but significantly on the number of fruits per plant, fruit weight per plant and fruit weight per plot. If applying the system without tillage, it must be followed by fertilizing NPK fertilizer at 375 kg/ha, if applying a minimum tillage system it must be followed by NPK fertilization at a dose of 375 kg/ha, but if applying the maximum tillage, it is enough to fertilizing NPK fertilizer at a dose of 125 kg/ha to obtain optimal number of fruits and tomato fruit weight. The highest yield was obtained in the combination of maximum tillage treatment with a fertilizer dose of 375 kg NPK/ha.